1994
DOI: 10.1002/cne.903420205
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of parallel fibres in the cerebellar cortex of the rat: An experimental light and electron microscopic study with biocytin

Abstract: Microinjections of biocytin have been made in the granular layer of the rat cerebellar cortex in order to label the axonal projections of a localised population of granule cells. Light microscopic techniques were used to determine the lengths of the parallel fibres and to measure the spacing and size of the fibre varicosities. Fibres were longest in the superficial one-third of the molecular layer, where mean overall length was 4.7 mm, and mean length decreased to 4.2 mm in the lower one-third of the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 21 publications
(23 reference statements)
7
104
1
1
Order By: Relevance
“…7 D, E). These fibers differed from the parallel fibers (Harvey and Napper, 1991) by their larger diameter (Ͼ1 m) and may correspond to a previously identified minor population of large fibers running parallel to the parallel fibers in the lower molecular layer (Pichitpornchai et al, 1994). The thickest portion of these axons could easily be followed for hundreds of micrometers (Fig.…”
Section: Organization Of the Lugaro Cell Axonal Plexusmentioning
confidence: 81%
See 1 more Smart Citation
“…7 D, E). These fibers differed from the parallel fibers (Harvey and Napper, 1991) by their larger diameter (Ͼ1 m) and may correspond to a previously identified minor population of large fibers running parallel to the parallel fibers in the lower molecular layer (Pichitpornchai et al, 1994). The thickest portion of these axons could easily be followed for hundreds of micrometers (Fig.…”
Section: Organization Of the Lugaro Cell Axonal Plexusmentioning
confidence: 81%
“…Our observations indicate that their length in rat is also in the millimeter range. A more precise value of 2 mm (half the length of the parallel fibers) can be taken from Pichitpornchai et al (1994), who found a small subpopulation of thick fibers running parallel to the parallel fibers in the lower third of the molecular layer and emitting short lateral branches, as reported by Fox (1959) for Lugaro cell axons.…”
Section: Organization Of the Golgi Cell-lugaro Cell Connectionmentioning
confidence: 99%
“…Ascending axon synapses were activated with electrodes placed in the GC layer, 30 -100 m directly behind the PC soma. Ascending axons make ϳ30 synaptic contacts before forming parallel fibers (Pitchitpornchai et al, 1994). Because parallel fibers make on average only one or at most two synapses with a single PC (Harvey and Napper, 1991), then in this configuration, the likelihood of activating parallel fiber synapses is small.…”
Section: Methodsmentioning
confidence: 99%
“…Except for a few hundred synapses associated with the climbing fiber input, all the remaining excitatory synapses originate from granule cells (Llinas 1990) with the majority associated with the parallel fiber segment of the granule cell axon (Harvey and Napper 1991). Each parallel fiber extends for several millimeters in a direction orthogonal to the planar structure of the Purkinje cell dendrite (Harvey and Napper 1991;Pichitpornchai et al 1994). The size of this synaptic input and the strict geometrical relationship between the associated axon and the Purkinje cell dendrite has been a dominate influence on all structural theories of cerebellar function (for review, see Bower 2002).…”
Section: Parallel Fiber and Ascending Segment Synapsesmentioning
confidence: 99%